MICROCLIMATE ENVELOPE SEBUAH APLIKASI KONSEP ARSITEKTUR BERKELANJUTAN - Burhanuddin, Burhanuddin (MEKTEK, 2011)
Exploitation of natural resources excessively can lower the quality of other natural resources on earth.Technology and the technology used by humans can cause negative impacts due to exhaust emissions, wastesthat pollute the environment. Microclimate Envelope is an application design that create a microclimate inthe building through its envelope formation.The use of the concept of